2019
DOI: 10.1016/j.jbiomech.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Development of a statistical shape-function model of the implanted knee for real-time prediction of joint mechanics

Abstract: Outcomes of total knee arthroplasty (TKA) are dependent on surgical technique, patient variability, and implant design. Non-optimal design or alignment choices may result in undesirable contact mechanics and joint kinematics, including poor joint alignment, instability, and reduced range of motion. Implant design and surgical alignment are modifiable factors with potential to improve patient outcomes, and there is a need for robust implant designs that can accommodate patient variability. Our objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Some examples in the bio‐medical field include, organ segmentation 47 , 48 , 49 and extraction of morphology from medical images 50 , 51 , 52 Only a limited number of studies have tried to combine statistical shape modeling with computational models, and are mainly found for orthopedic applications. For example, statistical shape models have been used for real‐time prediction of knee joint mechanics, 53 predicting femur bone strength, 54 or creating parametric models to model cervical spine loading. 55 The study by Bredbenner et al 55 introduced uncertainty in geometry considering cervical spines that were 1 from the mean shape, and showed that shape variation influenced the computed axial, flexion‐extension, and lateral displacements.…”
Section: Discussionmentioning
confidence: 99%
“…Some examples in the bio‐medical field include, organ segmentation 47 , 48 , 49 and extraction of morphology from medical images 50 , 51 , 52 Only a limited number of studies have tried to combine statistical shape modeling with computational models, and are mainly found for orthopedic applications. For example, statistical shape models have been used for real‐time prediction of knee joint mechanics, 53 predicting femur bone strength, 54 or creating parametric models to model cervical spine loading. 55 The study by Bredbenner et al 55 introduced uncertainty in geometry considering cervical spines that were 1 from the mean shape, and showed that shape variation influenced the computed axial, flexion‐extension, and lateral displacements.…”
Section: Discussionmentioning
confidence: 99%
“…These studies used SSM and FEA to: investigate the relationship between patellofemoral shape and function 48 ; force-displacement behavior of proximal femurs 49 ; to investigate cervical spine loading, 50 or for real-time prediction of joint-mechanics. 51 Literature that combines SSM with FEA/CFD simulations is more scarce in the field of cardiovascular biomechanics. To our knowledge, only Khalafvand and colleagues used a SSM in combination with CFD simulations.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have extended this technique to relate joint shapes with their function, resulting in statistical shape and function models. Examples include the relationship of knee anatomy with tibiofemoral and patellofemoral kinematics [28], total knee arthroplasty geometry and alignment with joint mechanics [29], and knee anatomy with knee laxity [30]. This paper aims to adapt shape-function statistical techniques to replace traditional calibration methods in the formulation of hip capsule models.…”
Section: Introductionmentioning
confidence: 99%